The Effect of Balance Training on Body Stability in Volleyball Athletes - Peri agusta simanjuntak; Zefanya silaban; Pebri Adi Lamtama Silaban; Jason Karunia One Jaya Gulo; Putri Paulina Marpaung; Randi Kurniawan; Deni Rahman Marpaung (STKIP Subang, 2026)
This literature review aims to synthesize current evidence regarding the effects of balance training on body stability in volleyball athletes. A systematic search was conducted using academic databases such as PubMed, Scopus, and Google Scholar to identify studies published between 2000 and 2024 related to balance training, postural control, and performance in volleyball. The reviewed studies consistently demonstrate that balance training significantly improves static and dynamic stability, neuromuscular coordination, and injury prevention. The analysis highlights that incorporating balance exercises into volleyball training programs enhances athletes’ ability to maintain postural control during dynamic actions such as jumping, landing, and rapid directional changes. Despite these benefits, limited literature specifically examines volleyball populations, suggesting a need for more sport-specific investigations. Overall, evidence supports the inclusion of structured balance training as a vital component of volleyball conditioning to enhancestability and minimize injury risks Furthermore, future research should focus on identifying the optimal duration, intensity, and type of balance exercises that yield the greatest improvements in volleyball-specific performance. Comparative studies between beginner, intermediate, and elite athletes would provide valuable insights into how training adaptations differ across skill levels. Additionally, integrating balance training with other conditioning elements such as strength, agility, and plyometric training could produce a more comprehensive understanding of its synergistic effects on athletic performance. These findings would contribute to the development of evidence-based training protocols aimed at maximizing performance outcomes and reducing injury incidence among volleyball players.